ANALYSIS OF PERFORMANCE MEASUREMENT USING THE BALANCED SCORECARD METHOD - Nurhayati, Nurhayati; Salim, Agus; Tonis, Marian; Handoko, Bobi (Universitas Islam Negeri Alauddin Makassar, 2023)
Background : Performance measurement plays a major role in the world of organizations, one of which is hospitals, due to the performance appraisal it can be seen the effectiveness of determining a strategy and its implementation within a certain period of time. Objective: The research objective was to determine the performance of Madani Hospital in Pekanbaru City using the Balanced Scorecard method. Method : The research was conducted using a quantitative method. Result : The results showed that the performance of Madani Hospital Pekanbaru City in terms of customers showed that inpatients expressed satisfaction with the services provided, although there were several indicators that were unsatisfactory, while from a financial perspective the economic ratios, efficiency and effectiveness were generally good, then the internal business perspective of the performance of RSD Madani Pekanbaru City can be seen from the ratios of BOR, ALOS, TOI, and BTO which show results that are not ideal values. From the ratio of GDR and NDR which shows good results, it means that the ratio of GDR and NDR in Pekanbaru City Hospital is ideal according to the provisions of the Directorate General of Community Health and Medical Services. Conclusion : Then the results of the study using the Balanced Scorecard approach can be concluded that the performance of Madani Hospital in Pekanbaru City with a score of 0.09 is included in the